Rigid pavements distresses - pavement condition index evaluation - Pereira, Tiago David da Costa Prudente (2015)
Pavements require maintenance in order to provide good service levels during their life period. Because of the significant costs of this operation and the importance of a proper planning, a pavement evaluation methodology, named Pavement Condition Index (PCI), was created by the U.S. Army Corps of Engineers. This methodology allows for the evaluation of the pavement condition along the life period, generally yearly, with minimum costs and, in this way, it is possible to plan the maintenance action and to adopt adequate measures, minimising the rehabilitation costs. The PCI methodology provides an evaluation based on visual inspection, namely on the distresses observed on the pavement. This condition index of the pavement is classified from 0 to 100, where 0 it is the worst possible condition and 100 the best possible condition. This methodology of pavement assessment represents a significant tool for management methods such as airport pavement management system (APMS) and life-cycle costs analysis (LCCA). Nevertheless, it has some limitations which can jeopardize the correct evaluation of the pavement behavior. Therefore the objective of this dissertation is to help reducing its limitations and make it easier and faster to use. Thus, an automated process of PCI calculation was developed, avoiding the abaci consultation, and consequently, minimizing the human error. To facilitate also the visual inspection a Tablet application was developed to replace the common inspection data sheet and thus making the survey easier to be undertaken. Following, an airport pavement condition was study accordingly with the methodology described at Standard Test Method for Airport Pavement Condition Index Surveys D5340, 2011 where its original condition level is compared with the condition level after iterate possible erroneous considered distresses as well as possible rehabilitations. Afterwards, the results obtained were analyzed and the main conclusions presented together with some future developments.